PROMOTION OF YOUTH INVOLVEMENT FOR EARLY SCHOOL LEAVING PREVENTION - Kanina, Inguna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Among the main challenges of contemporary education system are raising the motivation to study, strengthening the bond between the student and the school and prevention of early school leaving. In Latvia as well as in the rest of Europe the percentage of early school leavers still remains high. According to Eurostat data the percentage of students having left school early in Latvia reached 8% in 2018. Moreover the Baltic Social studies stated that altogether 26% of schools have faced the problem of early school leavers. Among the main factors reported as the reason for early school leaving are lack of motivation and risks related to school environment. Using the competency-based learning model new educational goals have been set, as follows, namely methodically moving towards the desired future profession, active involvement in the community, cooperation and developing of the feeling of patriotism. Lielvarde municipality in cooperation with the Ministry of Education and Science has launched a project aimed to gain a better understanding of students’ emotional and mental state, plans for the future as well as raising awareness of possible ways to get support during difficult times. The method used in the research were questionnaires. In the research there were involved students from all schools of Lielvārde district starting with age 13. The main goal of the research is to create a sustainable action plan, in order to gain more involvement from students. The results of research reveal students’ attitude towards studying, their future job options as well as the awareness of possibilities to use support systems in their lives.